Eddy dissipation modeling of turbulent non-premixed combustion with radiation effect using openfoam - Hassan Mohamed Kassem, Hassan Ibrahim (2011)
The Eddy dissipation model is one of the popular turbulent combustion models owing to its reasonable computational cost and accuracy. The purpose of this study is to implement the eddy dissipation model in OpenFOAM which is an open source code. It was implemented in many commercial CFD codes but it is the first time to be implemented in OpenFOAM. The model was implemented in new solver; EdmFoam. This new combustion solver was linked to radiation models library in OpenFOAM. EdmFoam solver was tested in modeling two different types of flames; jet flame and swirling flame. Each case was performed with and without radiative heat transfer modeling. The results were extensively compared against experimental measurements for temperature, mixture fraction and flame length. The predicted values showed that the model was implemented successfully. The results have a reasonable agreement with the experimental results. The results prove that a strong relation between the eddy dissipation model and the turbulence model behavior exists. The numerical predictions showed the importance of radiation modeling for the combustion cases.